Structural basis for the dephosphorylating activity of PTPRQ towards phosphatidylinositide substrates. (30th July 2013) - Yu, Keum Ran; Kim, Young Jun; Jung, Suk‐Kyeong; Ku, Bonsu; Park, Hwangseo; Cho, Sa Yeon; Jung, Hyeyun; Chung, Sang J.; Bae, Kwang Hee; Lee, Sang Chul; Kim, Bo Yeon; Erikson, Raymond L.; et al.
<x xml:space="preserve">Abstract</x> Unlike other classical protein tyrosine phosphatases (PTPs), PTPRQ (PTP receptor type Q) has dephosphorylating activity towards phosphatidylinositide (PI) substrates. Here, the structure of the catalytic domain of PTPRQ was solved at 1.56 Å resolution. Overall, PTPRQ adopts a tertiary fold typical of other classical PTPs. However, the disordered M6 loop of PTPRQ surrounding the catalytic core and the concomitant absence of interactions of this loop with residues in the PTP loop results in a flat active‐site pocket. On the basis of structural and biochemical analyses, it is proposed that this structural feature might facilitate the accommodation of large substrates, making it suitable for the dephosphorylation of PI substrates. Moreover, subsequent kinetic experiments showed that PTPRQ has a strong preferences for PI(3, 4, 5)P3 over other PI substrates, suggesting that its regulation of cell survival and proliferation reflects downregulation of Akt signalling.